2023
DOI: 10.1021/acs.jafc.3c02023
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Underlying the Effects of the Green Tea Polyphenol EGCG in Sarcopenia Prevention and Management

Abstract: Sarcopenia is prevalent among the older population and severely affects human health. Tea catechins may benefit for skeletal muscle performance and protect against secondary sarcopenia. However, the mechanisms underlying their antisarcopenic effect are still not fully understood. Despite initial successes in animal and early clinical trials regarding the safety and efficacy of (−)-epigallocatechin-3-gallate (EGCG), a major catechin of green tea, many challenges, problems, and unanswered questions remain. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 234 publications
0
0
0
Order By: Relevance
“…However, the clinical data of antidiabetic drugs on DS is still insufficient, with contradictory findings in different studies. In recent years, an array of natural compounds, including resveratrol, curcumin, geniposide, catechin, and flavonoids, have demonstrated potential in the prevention and management of sarcopenia. Our former research found that d -pinitol (DP) had hypoglycemic activity and cardioprotective effect in diabetic mice. , DP has a wide range of plant sources in nature, mainly found in Vigna sinensis , soybean, and pine plants. This compound is endowed with various physiological activities, such as insulin sensitization, hypoglycemic, antioxidation, anti-inflammatory, and antitumor effects, among others.…”
Section: Introductionmentioning
confidence: 99%
“…However, the clinical data of antidiabetic drugs on DS is still insufficient, with contradictory findings in different studies. In recent years, an array of natural compounds, including resveratrol, curcumin, geniposide, catechin, and flavonoids, have demonstrated potential in the prevention and management of sarcopenia. Our former research found that d -pinitol (DP) had hypoglycemic activity and cardioprotective effect in diabetic mice. , DP has a wide range of plant sources in nature, mainly found in Vigna sinensis , soybean, and pine plants. This compound is endowed with various physiological activities, such as insulin sensitization, hypoglycemic, antioxidation, anti-inflammatory, and antitumor effects, among others.…”
Section: Introductionmentioning
confidence: 99%
“…EGCG is the main polyphenol in green tea and has many biological functions. Not only does it play a crucial part in combating cancer [11][12][13][14] but it also plays a significant role in reducing inflammation [15,16] and has antibacterial, anti-infection, and other aspects. It is believed that EGCG will have great development prospects as a new drug in the future.…”
Section: Introductionmentioning
confidence: 99%